Ankle-brachial index in diabetic patients - which uppercut-off value is to be used? - Homza, Miroslav; Machaczka, Ondřej; Porzer, Martin; Kozák, Milan; Plášek, Jiří; Šipula, David (Bratislavské lekárske listy, 2018)
OBJECTIVES: In diabetic patients, there is a discrepancy in guidelines for ankle-brachial index (ABI) screening for peripheral arterial disease (PAD). While diabetes organizations suggest the value of upper limit of normal ABI to be 1.3, cardiologists recommend 1.4. Also, guidelines recommend using the higher value of ankle pres-sure (HAP) but multiple recent studies propose the opposite (LAP). METHODS: In this prospective study, we performed ABI measurements in 62 diabetic patients. Results were calculated by comparing higher and lower values of ankle pressure to those of duplex ultrasound (stenosis ≥ 50 % was considered PAD). Special attention was paid to patients with high and non-measurable ABI.RESULTS: LAP ABI appears to be a preferable method for PAD screening in diabetics. The upper cut-off value of 1.4 yielded better results with sensitivity of 93 % and negative predictive value of 91 %. No limbs with ABI between 1.3 and 1.4 with signifi cant stenosis were found. However, using HAP for the upper cut-off captured additional PAD patients. PAD was abundant among patients with high or non-measurable ABI.CONCLUSIONS: LAP should be used for assessing low ABI (cut-off 0.9) while HAP for detecting the abnormally high ABI. The preferable high ABI cut-off is 1.4. Condition with abnormally high or non-measurable ABI should be considered as PAD (Tab. 3, Ref. 22). Text in PDF www.elis.sk.KEY WORDS: ankle-brachial index, diabetes, peripheral arterial disease, lower extremity arterial disease, cut-off.
Keywords: Diabetic Angiopathies; diabetické angiopatie; onemocnění periferních cév; prediktivní hodnota testů; Ankle Brachial Index; Peripheral Vascular Diseases; Prospective Studies; lidé; tlakový index kotník-paže; Predictive Value of Tests; Humans; prospektivní studie